Status Partisipasi dan Kualitas Hidup Peserta Pos Pelayanan Terpadu Lanjut Usia - Dewi, Syamsumin Kurnia; Kusnanto, Hari; Pramantara, I Dewa Putu; Rahayujati, Theodola Baning (Universitas Ahmad Dahlan, 2017)
Background: Demographic and epidemiologic transition now occurred in the District of Bantul could be followed by decreasing quality of life in elderly. Community elderly care service (CECS) is a primary service for elderly with potential to support increasing quality of life in elderly. Based on previous study, utilization of CECS was high (73.30%) at subdistrict of Bambanglipuro, Bantul. To know the relationship between participation status and quality of life in CECS participants at subdistrict of Bambanglipuro. Method: A cross-sectional study was conducted from April to May 2012. Samples were selected with consecutive sampling technique. Data were collected from 8 CECSs at subdistrict of Bambanglipuro. Quality of life was measured with short form 36 (SF-36) Health Survey, including physical component summary (PCS) and mental component summary (MCS). Data then were analyzed with descriptive and analytic methods using Chi-square test and multiple logistic regression. Results: Of 238 subjects investigated, 186 (78.20%) were good in PCS and 194 (81.50%) were good in MCS. Multivariate analysis showed that active in physical exercise of CECS program, absence of hypertension, and better economic status were related to better PCS (aPR: 5.31, 95%CI: 2.52-11.20; aPR: 3.41, 95%CI: 1.31-5.47; aPR: 2.68; 95%CI: 1.31-5.47) and better MCS (aPR: 3.97, 95%CI: 1.83-8.64; aPR: 3.08, 95%CI: 1.39-6.82; aPR: 6.38; 95%CI: 2.62-15.53). Conclusion: Dominant factors that related to better quality of life in CECS participants were: active in physical exercise program of CECS, absence of hypertension and better economic status.